Shaikh Al-Fadhali's Thesis in Parsing the phrase 'No god but Allah' written by Al-Shaikh Saif-el-Deen Atta Abu-el Futouh Al-Wafa'y Al- Fadhali (1020 A.D.) (Journal of the College of Education for Women, 2019)
AbstractPraise be to Allah, The Lord of the worlds, and peace be uponMuhammad the master of former and latter people, and peace be upon Hisrelatives, companions and those who followed Him to Judgment day.After recognizing the prescription which is called (Al- Fadhaly's Thesis inparsing of "There is no god but God") as it is related with the word of theinvestigation of this issue attracted me, as being related with the idea of theonly one God that is mentioned in the prophetic speech, which is said byAnas- God satisfies him- Who said, Said the Messenger Muhammad peacebe upon him " Goes out of the Hell who said: there is no god but God, and inhis heart a hair weight of charity, and goes out of the Hell who said: there isno god but God, and in his heart a particle of charity, and goes out of the Hellwho said: there is no god but God, and in his heart as an atom's weight ofcharity. As that word, i.e.: there is no god but God, is the first part of the fiveprincipals of Islam, Thus, I wished to shed light on that prescription; in orderthat everyone who is specialized in Arabic language science could make useof it. And, as it contains the parsing of "There is no god but God" plus theviews that are said in that, I have obtained that prescription from the Azhar-Library on line. And my work was as the following:After this introduction, I have divided my research into two:The first division:The study division: which involves two divisions:The first: the writer's life.The second: Description of the prescription and the two curricula ininvestigation.The second division is the investigation of the bookThe list of the resources and sources.And after that humble effort in frond of God's majesty-there is no godbut God- I ask God to make my work this in my scale of charities in time whenthere is no benefit neither from fortune nor from sons except that who facedGod with god heart. Praise to God former and latter.